Effects of jump training on jumping performance of handball players: A systematic review with meta-analysis of randomised controlled trials. Issue 4 (August 2020) - Ramirez-Campillo, Rodrigo; Alvarez, Cristian; Garcia-Hermoso, Antonio; Keogh, Justin WL; García-Pinillos, Felipe; Pereira, Lucas A; Loturco, Irineu
This study aimed to assess the effects of jump training on the jumping performance of handball players compared with a control condition. The data sources utilised were PubMed, MEDLINE, Web of Science Core Collection and SCOPUS. Only peer-review randomised controlled trials were included. The inclusion criteria comprised: a jump training programme of at least 2 weeks; a control group; the assessment of the countermovement jump. The Physiotherapy Evidence Database scale was used to assess the risk of bias and methodological quality of eligible studies included in the meta-analysis. Risk of publication bias across studies was assessed using the extended Egger's test. Cohen's d effect sizes (ESs) were calculated from the countermovement jump and presented together with 95% confidence intervals (CIs). From 6108 records initially identified through database searching, 5 were eligible for meta-analysis. A significant improvement in countermovement jump height was observed, corresponding to 6.4 cm (95% CI = 4.9–7.9; Z  = 8.4, p  < 0.001), showing moderate heterogeneity ( I 2  = 51.4%). The magnitude of the main effect was very large (ES = 2.2 (95% CI = 0.95–3.4), Z  = 3.5, p  < 0.001). Jump training is effective in increasing vertical jump performance in handball players. However, the insufficient number of studies conducted precluded analyses of moderator variables. In future, researchers are advised to conduct jump training studies of high methodological quality (e.g. randomised controlled trials) and assess different jump exercise prescriptions across handball players of different sexes, ages and competitive levels to analyse if exercise prescription and player characteristics may influence training responses.